Creating leadership minds for the digital VUCA world - sculpting functional perceptual architectures via cultural expertise. (26th July 2021) - Breninger, Birgit
Few phenomena have incited as much passion as the unravelling of what 'effective leadership' means in constantly changing environments. It is suggested here that for leading successfully in the digital VUCA a fundamental transformation of individual minds is necessary, due to the novel bio-cultural paradoxes posed by it. Such 'VUCA resilient' minds are claimed to emerge from a specific perceptual architecture built on new, functional connections set up via the integration of cultural otherness into highly interlinked perception, cognition, affect and action systems. The relevant neurobiological underpinnings of this architecture biasing vision are outlined and an innovative perceptuo-cognitive experimental pilot (n = 34) is introduced to visualise the resultant changes in vision. Eyetracking (implicit) and questionnaire (explicit) data are analysed in tandem to improve the quality of data. Based on such promising initial tendencies it is suggested to add visual tools to leadership assessments.